Night in the American village : women in the shadow of the U.S. military bases in Okinawa - Johnson, Akemi (New York, NY : New Press, 2019)
"An examination of the complex relationship between the women living near the U.S. base in Okinawa and the servicemen who are stationed there."
Rina -- Eve -- Ashley -- Sachiko -- Arisa -- Suzuyo -- Daisy -- Miyo -- Kiki -- Chie -- Ai.
Includes bibliographical references.
Online resource; title from PDF title page (EBSCO, viewed May 7, 2019).
eBooks on EBSCOhost
Keywords: Military bases, American -- Social aspects -- Japan -- Okinawa-ken.; Women and the military -- Japan -- Okinawa-shi (Japan); Soldiers -- Sexual behavior -- United States; Women -- Japan -- Okinawa-shi -- Social conditions; Women -- Japan -- Okinawa-shi -- Interviews; Prostitution -- Japan -- Okinawa-shi.; Sex crimes -- Japan -- Okinawa-shi -- Anecdotes; Bases militaires américaines -- Aspect social -- Japon -- Okinawa (Ken); Femmes -- Japon -- Okinawa -- Conditions sociales; Femmes -- Japon -- Okinawa -- Entretiens; Violence sexuelle -- Japon -- Okinawa -- Anecdotes; BIOGRAPHY & AUTOBIOGRAPHY -- Social Scientists & Psychologists; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; Military bases, American -- Social aspects; Prostitution; Sex crimes; Soldiers -- Sexual behavior; Women; Women and the military; Women -- Social conditions; Japan -- Okinawa-ken; Japan -- Okinawa-shi; United States; POLITICAL SCIENCE / International Relations / General; Anecdotes; Interviews